UiO-66/Palygorskite/TiO2 Ternary Composites as Adsorbents and Photocatalysts for Methyl Orange Removal - Thaleia Ioannidou; Maria Anagnostopoulou; Dimitrios Papoulis; Konstantinos C. Christoforidis; Ioanna A. Vasiliadou (Applied Sciences, 2022)
Metal–organic frameworks are recognized as a new generation of emerging porous materials in a variety of applications including adsorption and photocatalysis. The present study presents the development of ternary composite materials made through the coupling of UiO-66 with palygorskite (Pal) clay mineral and titanium dioxide (TiO2) applied as adsorbent and photocatalyst for the removal of methyl orange (MO) from aqueous solutions as a typical anionic dye. The prepared materials were characterized using XRD, ATR, DR UV/Vis, and TGA analysis. Detailed kinetic experiments revealed that the presence of the clay at low amounts in the composite outperformed the adsorption efficiency of pure UiO-66, increasing MO adsorption by ca. 8%. In addition, coupling Pal/UiO-66 with TiO2 for the production of ternary composites provided photocatalytic properties that resulted in complete removal of MO. This was not observed in the pure UiO-66, the Pal/UiO-66 composite, or the pure TiO2 material. This study presents the first example of clay mineral/MOF/TiO2 composites with improved performance in removing dyes from aqueous solutions and highlights the importance of coupling MOFs with low-cost clay minerals and photocatalysts for the development of multifunctional advanced composites.